Pocket EMG - Wisotzky, Eric; Tseng, Victor; Pohlman, Dane (Demos Medical Publishing, LLC, 2015)
Pocket EMG is a practical reference intended for on-the-job use. It is designed as a portable pocket guide to performing nerve conduction and needle EMG studies in a fast-paced clinical environment. Each test is presented on a page, and includes a photograph of the proper set-up, indications for performing the test, and clinical pearls to help the learner appreciate the key technical points and physiological considerations. Quick reference tables are provided in the final two sections to summarize what tests should be ordered for particular problems or diagnoses and normal value ranges for all.